Ritual Kinship among Hindu Pilgrimage Priests of Allahabad - Boisvert, Mathieu (Anthropologica, 2017)
The primary objective of this article is to clarify the elements that contribute to the formation of the identity of the pilgrimage priests of Prayāga (Allahabad, Uttar Pradesh, India). This identity is constructed by the self-perception of the priests, the perception of this group by others, the various functions and directives at the core of the group’s professional activities, and the types of relationships the priests share with other social groups. I will discuss endogamy, the exclusivity of the profession, and commensalism and rites of passage, as well as certain elements specific to the prayāgavāla that unite them with the pilgrims. This article concludes that these pilgrimage priests form a relatively homogeneous and distinct social group whose identity is still deeply rooted in a traditional Hindu structure.